Large Median lobe leading to bilateral ureteric injury in RARP (Robot Assisted Radical Prostatectomy) - Abhishek Singh; Vivek Paharwar; Deval Parikh; Arvind Ganpule; Ravindra Sabnis; Mahesh Desai (Urology Video Journal)
Introduction: A technically challenging situation when dealing with prostate cancer is having large median lobes. Patients with large median lobes often have larger prostates, which makes it difficult to visualize anatomical planes during robot-assisted radical prostatectomy (RARP).Ureteric injuries are rare, most commonly secondary to iatrogenic injury with a reported rate of up to 0.3% following radical prostatectomy (RARP).The management of a ureteral orifice injury occurring during robotic radical prostatectomy (RARP) represents a challenge for urologists.Both the above situation requires expert hands to deal it properly and uneventfully. Methods: Here we demonstrate a 65 year male with localized Ca prostate with a large protruding median lobe.During posterior dissection bilateral Ureteric orifices weren’t identified and got incorporated in the incision.Here, we demonstrate how a median lobe leads to a dangerous complication and ways to overcome this situation by prompt identification of the complication and dealing with it with bilateral DJS stent, relocation of ureteric opening and ureteric orifice-plasty (new ureteric opening made). Results: Patient was well post op. catheter removed after 10 days, DJS removed after 4 weeks.There was no Hydrouretero-nephrosis on serial follow up, with Serum creatinine of < 1mg/dl. Conclusion: Ureteric injuries are rare (0.3%) after RARP, Preoperative planning with good imaging and Cystoscopy are mandatory.Intraoperative identification of ureteric injury, prompt detection and dealing with bilateral Double J Stenting, ureteric orifice- plasty is the key for successful management.